PENGARUH FLASH SALE DAN GRATIS ONGKOS KIRIM TERHADAP KEPUTUSAN PEMBELIAN PADA PENGGUNA E-COMMERCE TIKTOK SHOP DI KOTA BENGKULU - Cristiawan, Muhammad Hardi; Bustami, Taufik (UM. Bengkulu, 2026)
This study aims to analyze the influence of flash sales and free shipping on purchase decisions among TikTok Shop e-commerce users in Bengkulu City, with a particular focus on students at Muhammadiyah University of Bengkulu. As one of the emerging e-commerce platforms, TikTok Shop frequently offers promotional strategies such as flash sales and free shipping to attract consumers. In today's digital era, such marketing approaches are considered effective in encouraging quicker and more impulsive purchasing decisions. This research employs a quantitative method with an explanatory approach. Data were collected through questionnaires distributed to 120 student respondents who have made purchases on TikTok Shop. The data analysis techniques include validity and reliability tests, classical assumption tests, multiple linear regression analysis, and both partial and simultaneous hypothesis testing. The results indicate that both flash sales and free shipping have a positive and significant influence, both partially and simultaneously, on purchase decisions. These findings demonstrate that promotional strategies like limited-time discounts and free delivery effectively enhance consumer desire and confidence to shop online. This study contributes valuable insights for business practitioners, particularly e-commerce managers like those at TikTok Shop, in better understanding consumer behavior and developing effective promotional strategies to boost sales. Keywords: Flash Sale, Free Shipping, Purchase Decision, TikTok Shop, E-Commerce